Differences in Split Times between the Elite Breaststroke Swimmers - Ana Vasic; Marko Djurovic; Dejan Madic; Tomislav Okicic (Journal of Anthropology of Sport and Physical Education, 2021)
The aim of this research was to determine the differences between the finalists and semifinalists of the 2019 World Championships in the 100 m breaststroke. The total sample of subjects included in the study consisted of 23 male participants of the 2019 World Swimming Championships, who were divided into two groups. The first group consisted of finalists (24.75 ± 1.58 years; n = 8), and the second group of semifinalists (25.00 ± 3.38 years; n = 15). The results are taken from the official website of the International Swimming Federation (FINA). The variables analyzed in this study are: Split 1 - first passing time of the 100 m breaststroke, Split 2 - second passing time of the 100 m breaststroke, T100 - total time of the 100 m breaststroke. All data were processed by statistical analysis one‐way ANOVA. The results of the research showed that there are no statistically significant differences between the final and semifinal groups in any of the examined variables, but there are evident numerical differences that are more pronounced in the Split 2 (F = 2.063; p = .166). Based on these results, it can be concluded that swimmers who excel in their abilities in the other 50 m of the race, or achieve better times in this segment of the race, will achieve a better final result.